WHO IS 'BEHAVIORAL'? COGNITIVE ABILITY AND ANOMALOUS PREFERENCES. Issue 6 (December 2013) - Benjamin, Daniel J.; Brown, Sebastian A.; Shapiro, Jesse M.
Abstract In this paper, we ask whether variation in preference anomalies is related to variation in cognitive ability. Evidence from a new laboratory study of Chilean high‐school students with similar schooling backgrounds shows that small‐stakes risk aversion and short‐run discounting are less common among those with higher standardized test scores. The relationship with test scores survives controls for parental education and wealth. We find some evidence that elementary‐school GPA is predictive of preferences measured at the end of high school. Two laboratory interventions provide suggestive evidence of a possible causal impact of cognitive resources on expressed preferences.